Ganglion cell tumours in the sella turcica in close morphological connection with pituitary adenomas - Matyja, Ewa; Maksymowicz, Maria; Grajkowska, Wiesława; Zieliński, Grzegorz; Kunicki, Jacek; Bonicki, Wiesław; Witek, Przemysław; Naganska, Ewa (Folia Neuropathologica, 2015)
Ganglion cell tumours in the sellar region are uncommon. They are usually associated with pituitary adenomas, while isolated ganglion cell neoplasms are extremely rare. We report the clinicopathological studies of five cases diagnosed as ganglion cell tumours located in the intrasellar region: four mixed/collision tumours composed of gangliocytoma and pituitary adenoma, and one isolated ganglioglioma unrelated to adenoma. Clinically, two patients presented with acromegaly, while three others were initially diagnosed as non-functioning adenomas. In four cases, the histopathological examination of surgical specimens revealed intermixed lesions composed of pituitary adenoma and ganglion cell elements. The adenomas appeared to secrete growth hormone. Electron microscopy enabled identification of the sparsely granulated somatotroph cells. Neoplastic neuronal lesions were composed of mature ganglion cells, including binucleate or multinucleate cells. In all cases, boundaries between adenomatous and gangliocytic components were not clearly demarcated, and numerous gangliocytic cells were closely intermingled with adenomatous tissue. One case lacked endocrine symptoms, and no pituitary adenoma was identified in the surgically excised material; it was finally diagnosed as low-grade ganglioglioma. The etiopathogenesis of ganglion cell neoplasms in the sellar region is not clearly defined. Our study revealed that if ganglion cell neoplasms were combined with adenoma, both neoplastic components were closely related to each other, and numerous neuronal elements were strictly intermingled with adenoma cells. Such a tissue pattern indicates that these neoplastic changes, including their common respective etiopathogeneses, are closely related. The identification of both components in sellar regions may have some nosological implications.